An Analytical Study of the Methodological Implications of the Concept of “Social Current” - Ali Ebrahim Pour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
“Study of (Social) Currents (Currentology)” has been a new concept in recent decades in the Iranian intellectual, cultural, and political literature. Due to its influential and efficient literature, it has become popular. However, the lack of a scientific and methodological discipline has made this literature extremely chaotic, shaky, and turbulent. Therefore, in order to get rid of these misunderstandings, it is necessary to provide a clear theoretical framework for this literature. Currentology seems to have to be studied with a second-rate perspective. Its purpose is to introduce "Studies of Currents" as a science, not a journalistic and rhetorical model. It is a science, the subject of which is "(Social) Currents". This article is written using a descriptive-analytical method and using library resources. Also, this article focuses on the methodological principle of the relation and proportion between 'method' and 'object' (in the theoretical foundations of science in Islamic tradition). By analyzing the components of the "(Social) Current" definition, it derives its methodological implications. Finally, it offers them in 30 titles. These methodological implications underlie the design of a scientific model favorable to “Study of (Social) Currents (Currentology)”.